Archetypal myth: goddess Durga and the resilient matriarch in Rani Manicka's The Rice Mother - Zamri, Muhamad Lothfi; Zainal, Zainor Izat (Universiti Putra Malaysia Press, 2018)
Ruthless victimization of women is often depicted in Malaysian fiction. Characterized by biasness and brutalities of a predominantly male-centred culture, this theme has been a central theme by writers coming from varied cultural and ethnic backgrounds that makeup Malaysia. Rani Manicka also incorporates such theme in her debut novel, The Rice Mother (2003). However, another theme that becomes prominent in this novel is the theme of resiliency – portrayed mainly through the matriarch figure, Lakshmi. Indeed, Lakshmi’s resilience has interesting affinity with Durga, a principal form of the Hindu goddess, and it is against this mythological archetype that we frame the reading of the novel. Ultimately, an understanding of this mythological archetype will provide a clearer lens with which to look at Manicka’s story, and thus, the reader will be able to see how she presents the greater purpose of this archetype: to promote the resiliency of the human spirit.